CONSISTENCY OF THE INSTRUCTIONS FOR THE USE OF PROSPECTIVES FOR DETERMINING THE AREA OF A PARALLELA AND TRIANGLE AREA FOR STUDENTS OF SDN 6 MATARAM - Sarjana, Ketut; Handayani, Endang P.; Aminah, Siti; Nuraini, Nuraini (PROGRES PENDIDIKAN, 2021)
The approach used in this research is a quantitative approach with a quasi-experimental research design. The purpose of this study was to test the consistency and effectiveness of the instruction manual for determining the area of a parallelogram and the area of a triangle for students of SD 6 Mataram. To achieve this goal, tools and instructions for use were used in learning for the 111th-grade students of SDN 6 Mataram and divided into 3 classes. Because the research was conducted during the COVID-19 pandemic, the media was designed to be a learning video that describes the use of props, and their operational guidelines are narrated in the video. The video that contains the use of the tool is considered very in accordance with the instructions for use|| props. The results of the evaluation showed that there was no significant difference in the mean scores of the three pairs of classes (significance level 5% |t_h | < t_table = 2,0002). On the other hand, the completeness obtained by students in each class is >80% (KKM=70). This means that there is complete student learning about the area of a parallelogram and the area of a triangle. Thus, it can be concluded that the teaching aids for determining the area of a parallelogram and the area of a triangle and the instructions for use are consistently effective in helping students achieve complete learning on the material for the area of a parallelogram and the area of a triangle.